(3TQM GdLGeY GdcHjQ ddTjHGfis - (3CMeO Hf Ydj GdnqQGRj, CHh HcQ GdLUGU,J (B370 (3g` s; (3CHh YHO Gddg eMeO Hf GdMSf Hf aQbO, GdTjHGfj,J (B189 (3g` s
(3ChdgG (B:s
(3HGH ef GdfcGM s
(3BNQgG (B:s
(3CKfGA GdcdGe Ydi HGH RcGI GdeGd s
(3GdfSNI HgG MhGTs
(3JbQjHkG jYJHQ eHOC GdLRA GdChds
(3bWYI efg eced ddLRA GdChds
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdMfajs